A numerical model for evaluating fire performance of composite box bridge girders. (February 2020) - Zhang, Gang; Kodur, Venkatesh; Song, Chaojie; He, Shuanhai; Huang, Qiao
Abstract: This paper presents an approach for evaluating fire performance of composite box bridge girders exposed to fire. The model takes into account critical parameters, namely, fire scenario, fire exposure length, load level, numbers of longitudinal stiffeners in web and bottom flange and web pattern, that influence fire performance of bridges. A three dimensional finite element model, developed in the computer program ANSYS, is applied to model the fire response of composite box bridge girders. The finite element model is validated by comparing predicted sectional temperatures and deflections from the model with fire test data generated from a test on box bridge girder. The applicability of the numerical model in practical application is illustrated through numerical analysis on a composite box bridge girder subjected to simultaneous structural loading and fire exposure. Results from the numerical study clearly show that fire severity, fire exposure length, load level, number of longitudinal stiffeners and web slenderness have significant influence on the fire resistance of composite bridge girders. Provision of longitudinal stiffeners can result in lower deflections; thus enhancing fire resistance. Further, inclined web (configuration) incorporated into sectional shape can enhance fire resistance of composite box bridge girders. Highlights: An approach for evaluating fire performance of composite box girders is presented. Fire behavior of composite box bridge girders is investigated. Effect of web patterns and stiffeners on fire resistance of girders is quantified. Failure criterion in fire exposed girders is discussed.